Teaching cognitive and affective empathy in medicine: a systematic review and meta-analysis of randomized controlled trials - Hazel L. Ngo; Nina Sokolovic; Jennifer M. Jenkins (Medical Education Online)
Purpose Empathy can be divided into cognitive empathy (CE) and affective empathy (AE). CE is defined as the accurate understanding and appropriate response to others’ thoughts whereas AE is defined as the accurate understanding and appropriate response to others’ emotions. The overall purpose of this systematic review and meta-analysis is to assess the effectiveness of empathy interventions in physicians and physicians-in-training in increasing CE and AE. Specifically, we are interested in examining whether specific teaching methods and intervention designs may contribute to greater empathy intervention effectiveness for CE and AE outcomes.Method Studies searched included randomized controlled trials conducted between 1971 to 2022 examining empathy interventions for medical students and physicians. Thirty-six studies, consisting of 3,833 participants, met the inclusion criteria. Data were analysed using random-effects pairwise meta-analysis.Results Empathy interventions have moderate effect sizes on both CE [d = .50 (95% CI = .30, .70)] and AE [d = .46 (95% CI = .30, .62)]. Heterogeneity of effects was evident for both analyses. The effectiveness of interventions on AE was moderated by measurement type. Intervention effectiveness was not significantly moderated by other intervention and study characteristics for either type of empathy.Conclusions There is evidence of key differences, and similarities, in how CE and AE is taught to medical students and professionals; however, the small number and high level of heterogeneity in studies makes this difficult to confirm. Research in this field will benefit from investigators standardizing teaching and research methods across studies.